HISPANICS IN TEXAS HIGHER EDUCATION: AN ASSESSMENT OF THE STATE â€œCLOSING THE GAPSâ€ INITIATIVE - Blount, Grady Price; Rodriguez, Robert G. (European Scientific Journal, ESJ, 2015)
Demographic changes associated with growth of the Hispanic and black population in the U.S. state of Texas have led politicians and policymakers to recognize that academic success in their ethnic and racial minority populations is a key to future statewide economic success. These demographic transitions require proactive state intervention to assure the earning power and intellectual prowess of the next generation. This study assesses the degree to which the Texas â€œClosing the Gapsâ€ initiative has addressed the disparities in higher education among the stateâ€™s diverse populations.